“To be, or not be… satisfied in NPOs”: a serial multiple mediation and clustering analysis of paid staff and volunteers' profiles - López-Cabrera, Rocío; Medina, Francisco J.; Euwema, Martin; Arenas, Alicia (Frontiers in Psychology, 2023)
Introduction Non-profit organizations (NPOs) are a complex working context whose main characteristic resides in the dichotomy between paid staff and volunteers. Despite its benefits for goal achievement, this circumstance can be also a challenge, for both groups' interaction, for their comprehension of their own role and to HR management. The aim of this study was to explore factors that may contribute to promote job satisfaction among NPOs' members. Methods Combining two different data analyses, serial multiple mediation analyses and cluster analyses, first we analyze whether there are differences between paid staff and volunteers in perceived intrapersonal conflict and performance and its effect on job satisfaction, and second, we analyze whether there is an additional profiles distribution that reflects more adequately the reality of NPOs, despite the formal roles that coexist in these organizations (paid staff and volunteers). Results Results confirm that paid staff and volunteers differ on their perceived job satisfaction level, with volunteers being more satisfied. This relationship is serially mediated by role conflict, role ambiguity, and performance. Another characteristic of the NPOs is that the dichotomy between paid staff and volunteers does not capture well the reality of the labor relations between members of both groups and the organization. To explore this phenomenon, we perform a cluster analysis based on paid staff and volunteers' perceptions. Cluster analyses demonstrate the existence of three rather homogenous profiles. Discussion Additionally, practical implications for HR management in NPOs and future research lines to understand this organizational context dynamics are also discussed.